Prognostic significance of HALP score in İdiopathic Pulmonary Fibrosis-related mortality - Çolak, Mustafa; Çoban, Hikmet; Sarıoğlu, Nurhan; Yumrukuz Şenel, Merve; Erel, Fuat (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2025)
Background and aim: To investigate the prognostic value of the HALP (Hemoglobin, Albumin, Lymphocyte, and Platelet) score for mortality in patients with Idiopathic Pulmonary Fibrosis (IPF). Methods: From November 2020, 39 patients with IPF were followed for a duration of 3 years. At the end of 3 years, the relationship between the initial HALP score and mortality was investigated. Results: Thirty-nine patients diagnosed with IPF were included in the study, 30 of whom were male. The average age of all patients was 68.79±7.08. At the end of the three-year follow-up period, 12 patients (33.3%) had died. When comparing patients who died and those who survived at the end of three years; significant differences were found in age, neutrophil, albumin, HALP score, FEV1%, FVC%, DLCO%, GAP score, and 6 MWD. ROC analysis for the HALP score’s predictive value for mortality yielded an AUC of 0.743 and p=0.011. For a cut-off value of HALP≤30.5, p=0.01, sensitivity and specificity were 61.54% and 92.31%, respectively. Multivariate analysis for predicting mortality found HALP≤30.50 as a significant risk factor (p=0.046). An increase of one monad at the HALP cut-off (≤30.50) score level reduced the risk of death by 9.57 times. It was observed that FVC%, DLCO% and 6 MWD were not risk factors in predicting mortality. (p=0.30, p=0.08, p=0.07). Conclusions: Our study suggests that the HALP score may serve as a negative prognostic biomarker that can be used to predict mortality in cases with IPF.